2015
DOI: 10.1016/j.jnucmat.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

In situ high temperature oxidation analysis of Zircaloy-4 using acoustic emission coupled with thermogravimetry

Abstract: h i g h l i g h t sThermogravimetry associated to acoustic emission (AE) improves knowledge on the corrosion of metals at high temperature. Kinetic transition is detected under air oxidation tests at 900°C of Zircaloy-4 by a change in the rate of mass gain and by the AE activity. AE analysis is complementary to characterizations of post mortem oxidized samples. AE allows us to distinguish the cracks which occur during the Zircaloy-4 oxidation from the cracks which arise during the cooling of the samples. a b s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Research has indicated this acceleration is associated with the formation of large cracks perpendicular to the metal-oxide interface, and the formation of a defective, heavily-fractured oxide layer [21,24,25]. Although in this study oxides are formed at a much lower temperature, the results could still be of value to research carried out at high temperatures.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Research has indicated this acceleration is associated with the formation of large cracks perpendicular to the metal-oxide interface, and the formation of a defective, heavily-fractured oxide layer [21,24,25]. Although in this study oxides are formed at a much lower temperature, the results could still be of value to research carried out at high temperatures.…”
Section: Introductionmentioning
confidence: 72%
“…In order to understand oxidation during loss of coolant accidents (LOCA) many authors have researched oxidation of zirconium alloys in the 600-1200°C temperature range [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In oxides formed on zirconium alloys cracks are known to form parallel and close to the metal oxide interface (N. P Platt et al, 2015;P. Platt et al, 2015a), and perpendicular to the metal-oxide interface at higher temperatures (Omar et al, 2015;Parry et al, 2013). In both cases these cracks are linked with a significant reduction in the protective capacity of the oxide layer.…”
Section: Damage Analysismentioning
confidence: 99%
“…To avoid mechanical and electromagnetic noise, the low-and high-filter frequencies were set as 0.1 MHz and 1 MHz, respectively. As the conventional piezoelectric transducer can only be used at ambient temperature, a waveguide with the good transmission of acoustic signals (low attenuation of the signal energy) was designed using Nichrome wire to resist the chemical corrosion (oxidative or reductive atmospheres) [26]. This waveguide connects the specimen and transducer perfectly, consequently avoiding the transducer locating at high temperatures.…”
Section: Acoustic Emission Monitoringmentioning
confidence: 99%